2010
DOI: 10.1186/1472-6920-10-68
|View full text |Cite
|
Sign up to set email alerts
|

Live lecture versus video podcast in undergraduate medical education: A randomised controlled trial

Abstract: BackgroundInformation technology is finding an increasing role in the training of medical students. We compared information recall and student experience and preference after live lectures and video podcasts in undergraduate medical education.MethodsWe performed a crossover randomised controlled trial. 100 students were randomised to live lecture or video podcast for one clinical topic. Live lectures were given by the same instructor as the narrator of the video podcasts. The video podcasts comprised Powerpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
183
1
21

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(216 citation statements)
references
References 19 publications
11
183
1
21
Order By: Relevance
“…This is particularly true with regard to the role of traditional, passive, didactic lectures, which, in spite of the large body of evidence indicating that they are a relatively ineffective way of maximising student learning and understanding (Bransford et al 2000, Frederick 1986, Stuart and Rutherford 1978, are still the primary mode of 'information transfer' utilised by most places of higher education. Indeed, their function becomes even less clear when one considers that students can now easily access a wealth of useful, and often better, educational information on the internet and, increasingly, can also view recorded lectures (Cardall et al 2008, Chandra 2011, Dupagne et al 2009, McNulty et al 2009, Schreiber et al 2010, Soong et al 2006, Traphagan et al 2010, Vaccani et al 2016, Young 2008. With these thoughts in mind, many educators are now utilising their relatively limited face-to-face time with students in a much more student-focussed manner in order to maximise their learning and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true with regard to the role of traditional, passive, didactic lectures, which, in spite of the large body of evidence indicating that they are a relatively ineffective way of maximising student learning and understanding (Bransford et al 2000, Frederick 1986, Stuart and Rutherford 1978, are still the primary mode of 'information transfer' utilised by most places of higher education. Indeed, their function becomes even less clear when one considers that students can now easily access a wealth of useful, and often better, educational information on the internet and, increasingly, can also view recorded lectures (Cardall et al 2008, Chandra 2011, Dupagne et al 2009, McNulty et al 2009, Schreiber et al 2010, Soong et al 2006, Traphagan et al 2010, Vaccani et al 2016, Young 2008. With these thoughts in mind, many educators are now utilising their relatively limited face-to-face time with students in a much more student-focussed manner in order to maximise their learning and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Students identified inappropriate teaching methods (15%) and large class room size with excessive disturbance (10.8%) barriers in class room learning. Some reports have shown that students' inactivity in traditional teacher-centered classes would make them bored and exhausted that consequently would decrease their concentration and learning and finally would result in their absence from the classroom 11 . A statically significant difference was found between the male and female students.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, along with others, elucidates that PRL implementation can provide additional, supplementary options of study methods for students (Cardall, Krupat, & Ulrich, 2008, Schreiber, Fukuta, Gordon, 2010. Although PRL may improve learning of factual details, its use in replacing LL may hinder students from conceptualizing complex information sometimes due to technical challenge (Rose, 2009).…”
Section: Study Dmentioning
confidence: 99%